Improving Students’ Learning Outcomes through Jigsaw Method: A Classroom Action Research at SMPN 8 Satap Woja - Kainati, Saidatul (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2023)
This research is prompted by the issues that arise at SMPN 8 Satap Woja, specifically the fact that after the teacher integrates English learning on the teacher-suggested materials, student learning outcomes remain low. That is evident from both the teacher's observations and the students' learning outcomes that merely a small number of students are engaged in class. Student activity is important to the learning process because it influences learning outcomes. In addition, student interest and response have a significant impact on the achievement of learning outcomes during the learning process. As a result of being aware of the aforementioned issues, a teacher feels compelled to improve lessons by conducting research. This study is a classroom action research utilizing the Jigsaw method to enhance student learning outcomes for at SMPN 8 Satap Woja. This study has been conducted in two cycles. Based on the analysis of data in this study, Jigsaw research could indeed improve student learning outcomes. The  implementation of the Jigsaw method model can increase student participation. The Jigsaw learning model can enhance student learning outcomes, as evidenced by the pre-test average of 47%, cycle 1: 58%, and cycle 2: 70.5%.